2016
DOI: 10.1075/sll.19.1.01bar
|View full text |Cite
|
Sign up to set email alerts
|

Indefiniteness and specificity marking in Catalan Sign Language (LSC)

Abstract: Bringing together the areas of sign language semantics-pragmatics interface and discourse reference, this article offers a description of how indefiniteness and (non‑)specificity is encoded in Catalan Sign Language (LSC). By using a combined methodology of corpus data and grammatical tests, the present study shows that the encoding of indefiniteness and specificity in LSC is achieved by three main means, namely lexical signs, the use of nonmanuals, and the use of signing space. The basic primitives required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…This latter, more iconic use of high space not only has a different interpretation, but involves different eye gaze behavior: it must be directed toward the sign DOG for the "physically high" interpretation. The iconic use contrasts with the high use of space for domain restriction, where gaze is toward the interlocutor (not the locus), as noted by Barberà 2012 for high existential quantifiers. All signers that we consulted indicated the complete unavailability of a widening domain interpretation for nouns like DOG with height.…”
Section: Domain Restriction In Aslmentioning
confidence: 91%
See 1 more Smart Citation
“…This latter, more iconic use of high space not only has a different interpretation, but involves different eye gaze behavior: it must be directed toward the sign DOG for the "physically high" interpretation. The iconic use contrasts with the high use of space for domain restriction, where gaze is toward the interlocutor (not the locus), as noted by Barberà 2012 for high existential quantifiers. All signers that we consulted indicated the complete unavailability of a widening domain interpretation for nouns like DOG with height.…”
Section: Domain Restriction In Aslmentioning
confidence: 91%
“…Others have argued that ASL is an 'NP language' in the typology argued for by Bošković (2005), concluding that all noun phrases in ASL are bare noun phrases, and such uses of IX are modifiers of some sort (Koulidobrova 2012) or demonstratives (Koulidobrova & Lillo-Martin 2016). Barberà (2015Barberà ( , 2012 "Mia loves the/that/SPEC woman"…”
Section: Background: Noun Phrases and Loci In Aslmentioning
confidence: 99%
“…Non-specific indefinite pronouns are commonly used in agent-backgrounding contexts (Barberà & Quer 2013). It has been reported that some sign languages may mark the distinction in specificity through the articulation of the indefinite noun phrase in different R-loci (high vs. low) and/or through the absence/presence of certain non-manual markers (Barberà 2012(Barberà , 2015. No comprehensive analysis of TİD indefinites is available yet; however, we discuss here our preliminary observations regarding the non-specific indefinite pronominals that our consultants produced during the elicitation tasks.…”
Section: Non-specific Indefinite Pronounsmentioning
confidence: 99%
“…14 We gloss this pronominal as ONElat-high and not as ONEup as in Barberà (2016), since articulation of these signs in the lateral vs. central space is crucial for our analysis. 15 We thank the editors for the suggestion of this term.…”
Section: Notesmentioning
confidence: 99%
“…3 and Fig. 4, that include sucking the cheeks in and pulling the mouth ends down, sometimes combined with a shrug (Barberà 2016). The most common environments in which both pronouns may be found are locative universals (Q7), indirect evidential existentials (Q3), vague and anchored existentials (Q2 and Q1), conditionals (Q11) and unrestricted universal contexts (Q9 and Q10).…”
Section: Indefinite Pronounsmentioning
confidence: 99%